2015
DOI: 10.1007/s10585-015-9773-7
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial mesenchymal-like transition occurs in a subset of cells in castration resistant prostate cancer bone metastases

Abstract: TGFβ is a known driver of epithelial-mesenchymal transition (EMT) which is associated with tumor aggressiveness and metastasis. However, EMT has not been fully explored in clinical specimens of castration-resistant prostate cancer (CRPC) metastases. To assess EMT in CRPC, gene expression analysis was performed on 149 visceral and bone metastases from 62 CRPC patients and immunohistochemical analysis was performed on 185 CRPC bone and visceral metastases from 42 CRPC patients. In addition, to assess the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…A recent gene expression analysis of CRPC tissues revealed a positive correlation between Twist expression and CRPC metastases. 23 Studies with TRAMP mice showed increased Twist expression in prostate tumors and its overexpression is associated with disease progression. 20 , 24 To further study the crosstalk between Skp2 and Twist as well as their requirements in the development and progression of CRPC.…”
Section: Resultsmentioning
confidence: 99%
“…A recent gene expression analysis of CRPC tissues revealed a positive correlation between Twist expression and CRPC metastases. 23 Studies with TRAMP mice showed increased Twist expression in prostate tumors and its overexpression is associated with disease progression. 20 , 24 To further study the crosstalk between Skp2 and Twist as well as their requirements in the development and progression of CRPC.…”
Section: Resultsmentioning
confidence: 99%
“…Transforming growth factor β (TGFβ) is a pivotal player that induces EMT in cancer cells (40). Increased expression of TGFβ and EMT-related proteins has been observed in CRPC bone metastasis (41). Interestingly, expression of SPOCK1 is elevated by TGFβ treatment in lung cancer cells, suggesting that SPOCK1 mediates downstream TGFβ signaling (33).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, through IHC, tumors were evaluated from YK-4-279-treated and untreated animals for the known EMT transcription factors Twist and Zeb (Figures 9 and 10), but found no difference in protein expression between treated and untreated groups. Further, nuclear staining for these EMT-associated transcription factors was only observed in a subset of cells within each tumor (Figures 9 and 10) (22). Interestingly, in the top 20 genes up-regulated in the PDX tumors after YK-4-279 treatment (Figure 8), a number of genes associated with the mineralocorticoid receptor (MR) were identified.…”
Section: Methodsmentioning
confidence: 99%